EQUALITY IN THE ALLOCATION OF SCARCE VACCINES - Saunders, Ben (Les ateliers de l'éthique / The Ethics Forum)

(untitled) (Centre de recherche en éthique (CRÉ), 2018)
In the event of a pandemic, demand for vaccines may exceed supply. One proposal for allocating vaccines is to use a lottery, to give all citizens an equal chance, either of getting the vaccine (McLachlan) or of surviving (Peterson). However, insistence on strict equality can result in seriously suboptimal outcomes. I argue that the requirement to treat all citizens impartially need not be interpreted to require equal chances, particularly where citizens are differently situated. Assuming that we want to save lives, we should also seek to use vaccine efficiently, so far as this is compatible with equality. Thus, in allocating vaccine, we may want to be sensitive to (i) different levels of need and/or (ii) effects on vaccine production. While such policies may result in unequal chances, they may even improve everyone’s chances. In such cases, the resultant inequality is not a violation of impartiality, but a consequence of considering each person’s claim seriously.